2019
DOI: 10.1155/2019/9545297
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Chemical Synthesis of Fondaparinux

Abstract: Fondaparinux (trade name Arixtra) is a safe and efficacious anticoagulant, and it is chemically related to low-molecular-weight heparins such as enoxaparin. Fondaparinux is a synthetic pentasaccharide, and its synthesis is difficult and expensive. The high cost of fondaparinux thwarts its extensive worldwide usage. Over the last two decades, several research groups and pharmaceutical companies have been interested in finding efficient and practical methods for its synthesis. The present review discusses those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As an extension of random glycosylation, Ding et al reported the double random glycosylation starting with an unprotected monosaccharide for the synthesis of a trisaccharide library. The target library and its synthesis through a double random glycosylation strategy is summarized in Scheme .…”
Section: Discussionmentioning
confidence: 99%
“…As an extension of random glycosylation, Ding et al reported the double random glycosylation starting with an unprotected monosaccharide for the synthesis of a trisaccharide library. The target library and its synthesis through a double random glycosylation strategy is summarized in Scheme .…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of this complex molecule on a commercial scale has asked for the development of sophisticated chemistry, which has been recently reviewed. 61,62 Different strategies have been developed for the assembly of Fondaparinux, using glucuronic and iduronic acid monosaccharides 63,64 or using a late-stage oxidation approach. 65,66 Nadji et al reported the synthesis of Fondaparinux (depicted in Scheme 4), that delivered the product on an industrial scale of 516 g in an overall 0.0338% yield over 28 steps, 67 which is one of the efficient methods for industrial grade synthesis.…”
Section: Heparin (Hp) and Heparan Sulfate (Hs)mentioning
confidence: 99%
“…3 Fondaparinux has 100% absolute bioavailability subcutaneously (SC), instant onset of action, a long half-life (terminal half-life of 17-21 hours), direct renal excretion, and fewer adverse reactions when compared with direct oral anticoagulants. [4][5][6] The efficacy and safety of fondaparinux in the prevention of VTE in lower extremities during major orthopedic surgeries and in high-risk abdominal surgery has been demonstrated in many clinical studies and it has been found to be superior or non-inferior to other antithrombotic agents. [7][8][9][10][11][12][13] For the past 2 decades, fondaparinux has been one of the mainstays for VTE prevention in acutely ill adult patients.…”
Section: Introductionmentioning
confidence: 99%